Punicalagin Inhibits Cell Growth and Promotes Apoptosis in Bladder Cancer T24 Cells via Upregulating Oxidative Stress and Apoptotic Marker Expressions - Gu, Junqing; Cai, Tao; Li, Yugen; Liao, Bo (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Bladder cancer is a prevalent form of cancer worldwide and is associated with increased rates of mortality. Objectives The present investigation focuses on understanding the inhibitory activities of punicalagin on the viability and promotion of apoptosis in T24 bladder cancer cells. Materials and Methods The punicalagin at diverse concentrations (1-15 μM) was tested for its in vitro free radical scavenging effects, including DPPH, superoxide and peroxyl radicals. The effects of punicalagin against the growth of bladder cancer T24 and normal Vero cells were tested using an MTT assay. The endogenous ROS production and apoptosis were tested using fluorescent staining methods. The tryphan blue staining was done to examine the cell adhesion and viability of the cells. The oxidative stress markers and apoptotic protein expression levels were assayed using kits. Results The results of the free radical scavenging assays revealed the effective antioxidant effects of the punicalagin, which reduced the DPPH, superoxide and peroxyl radicals. The treatment with diverse doses of punicalagin effectively inhibited the T24 cell growth while not disturbing the non-malignant Vero cell growth. Punicalagin effectively increased endogenous ROS accumulation and apoptosis in the T24 cells. The cell adhesion and growth was effectively reduced by the punicalagin treatment. It also increased the levels of oxidative stress markers and promoted apoptotic protein expression in the T24 bladder cancer cells. The outcomes of the punicalagin treatment were supported by the findings of the standard drug DOX treatment. Conclusion Altogether, the current exploration discovered that punicalagin has anticancer properties that inhibit viability and promote apoptosis in T24 bladder cancer cells via upregulating oxidative stress and apoptotic protein expressions. Therefore, the current results suggest the punicalagin as a promising and candidate for bladder cancer treatment.
Keywords: Apoptosis; Oxidative stress; Caspases; Punicalagin; Bladder cancer